Acute and short-term effects of Lactobacillus paracasei subsp. paracasei 431 and inulin intake on appetite control and dietary intake: A two-phases randomized, double blind, placebo-controlled study. (1st February 2022) - NabizadehAsl, Laleh; Sendur, Suleyman Nahit; Ozer, Barbaros; Lay, Incilay; Erbas, Tomris; Buyuktuncer, Zehra
Abstract: This study aims to examine the acute and short-term effects of prebiotics, probiotics, and their combination on appetite, energy intake and satiety related hormones in two phases. The first phase was a randomized, double blind, placebo controlled crossover study. Prebiotic (16 g inulin), probiotic ( Lactobacillus paracasei subsp. paracasei 431 ( L. casei 431) (>10 6  cfu/ml), synbiotic (their combination) and control (16 g maltodextrin) dairy drinks were consumed by 16 healthy men with a standard breakfast on four separate test days, and the following satiety responses and ad libitum food intake at lunch and over 24 h were assessed. In the second phase, the effects of 21 days of synbiotic (n = 10) or control (n = 11) drink consumption on appetite sensation, energy intake, serum glucose, insulin, peptide YY, ghrelin, obestatin and adiponectin concentration were assessed in a randomized double-blind placebo-controlled design. In the first phase, energy intake values during ad libitum lunch were the lowest in the prebiotic drink, followed by probiotic, synbiotic and control drinks, respectively (p = 0.017); also the rest of the day and 24-h dietary energy intake was lower by prebiotic and probiotic drinks compared to the control drink (p < 0.05 for each). For short-term effects, no significant difference in anthropometric measurements, hunger-satiety scores and serum glucose, insulin, PYY, ghrelin, obestatin and adiponectin concentrations were recorded. Despite the potential of prebiotics and probiotics to reduce energy intake, further studies are required for a better understanding of their role in satiety related mechanisms.